1865 Fla. Laws 23, 25-27. - (:unkn) unknown (My University, 1866)
An Act Prescribing Additional Penalties for the Commission of Offences against the State, and for Other Purposes, Ch. 1460, No. 3, § 15: That if any person shall form any military organization in this State, not authorized by law, or shall participate or aid or abet in the formation of such organization, he shall be deemed to be guilty of a misdemeanor, and upon conviction shall be fined in a sum not exceeding one thousand dollars, and imprisoned for a term not exceeding six months;
Keywords: MILITIAS